Analysis and experiment of auxetic centrifugal softening impact energy harvesting from ultra-low-frequency rotational excitations. (1st February 2023) - Fang, Shitong; Chen, Keyu; Lai, Zhihui; Zhou, Shengxi; Liao, Wei-Hsin
Abstract: The ubiquitous ultra-low-frequency rotational motions have become a kind of potential source for energy harvesting. Despite this, achieving high energy output at ultra-low rotational frequencies via simple energy harvesting structures appears to be a significant challenge. Therefore, this paper proposes an auxetic centrifugal softening impact energy harvester (ASIEH) to break through this bottleneck. The ASIEH consists of a centrifugal softening driving beam that impacts two rigid auxetic piezoelectric beams to generate electric energy during rotation. The modeling and simulation of the ASIEH and the plain centrifugal softening impact energy harvester (PSIEH) indicate that the high stress distribution and the simultaneous operation of d 31 and d 32 modes of the auxetic energy harvester can improve the energy output. Under the centrifugal effect, the driving beam experiences the vibration, impact and trapping modes subsequently, among which the impact mode produces the highest energy output. Experiments are conducted to validate the model and show that the peak power of the ASIEH (0.673 mW) can be increased by 200.45% compared with that of the PSIEH (0.224 mW) at 3.5 Hz. Parametric studies indicate that no matter how the impact distance and rotational radius are varied, the peak power and bandwidth of the ASIEH are higher than those of the PSIEH. Owing to the combination of both the centrifugal effect and the auxetic structure, the proposed ASIEH exhibits the great potential in ultra-low-frequency rotational energy harvesting with both high power density (41.23 μ W/g) and high output power. Highlights: An auxetic centrifugal softening impact energy harvester is proposed. A breakthrough of the energy output bottleneck with centrifugal effect is achieved. Modeling and simulation are performed to explain the operating principle of harvester. Experiments and parametric studies are conducted to validate the proposed design. The proposed harvester has both high power density (41.23 μ W/g) and high output power.